The significance of biological bases in maize production - Krivián, Ágnes (Acta Agraria Debreceniensis, 2013)
The comparative trial has been set up in the Demonstration Garden of the Institute of Crop Sciences of the University of Debrecen, Centre for Agricultural and Applied Economic Studies, Faculty of Agricultural and Food Sciences and Environmental Management in 2012, with 24 hybrids with different genetic characteristics and growing periods. The soil of the trial is lime-coated chernozem, with a humus layer of 50–70 cm. The weather of the trial year was quite droughty; the monthly average temperature was 3–4 oC higher than the average of 30 years. High temperature, together with lack of precipitation occurred during the most sensitive phenophases of maize (flowering; fecundation, grain saturation). The following characteristics have been observed: starting vigour, date of male and female flowering, plant and cob height, dry-down dynamics during maturation and the change of yield composing elements has also been quantified. The yield was recalculated to 14% moisture content grain yield after harvesting. The beginning of the growing period was advantageous, therefore the analysed hybrids could grow a high (above 300 cm) and strong stem. The yield of the hybrids changed between 10.33 and 11.87 t ha-1, but as a result of the unfavourable climatic extremes, their genetic yield potential prevailed only at a rate of 30–40%. However, moisture content by the time of harvesting was good despite its early date (12th September); it remained under below 14% in most cases. Dry-down was measured on a weekly basis between 14th August and 5th September. The analysis of the qualitative parameters of the maize hybrids (protein %, oil % and starch %) resulted in significant differences. The most significant difference has been observed in the case of protein content (LSD5%=2.01). Oil content was the most advantageous in the case of hybrids belonging to the mid-late growing group (FAO 400). The X9N655 and 36V74 hybrids had the highest oil content (around 4%), while hybrids P9915 and 37F73 had significantly lower oil content. Starch content was above 70% in the case of every hybrid. Hybrid selection is highly important in terms of yield and yield security of maize, as well as the application of modern biological fundamentals and hybrid specific technology for the improvement of the level of cultivation technology.